Two-dimensional early thermal crack analysis of concrete structures by finite element method. (15th July 2017) - Kwan, A.K.H.; Ma, F.J.
Highlights: Early thermal cracking of concrete affects serviceability and durability. A FE method with crack queuing is applied to early thermal crack analysis. Two-dimensional wall and slab panels with movement restraints are analysed. Discrete crack pattern, crack length and maximum crack width are obtained. Abstract: Early thermal cracking of concrete often causes serious serviceability and durability problems, and thus should be carefully analysed and properly controlled. However, discrete crack analysis for the determination of crack pattern and widths is rather difficult because stress relief occurs during crack formation, and if the stress relief is not immediately accounted for, many unrealistic parallel cracks will be formed. Herein, the finite element method is augmented with a crack queuing algorithm to deal with the stress relief during cracking for the analysis of early thermal cracks. With this new finite element method, well-defined crack patterns are obtainable for determination of crack widths. Comparison with the predictions by design codes verified that the crack patterns and widths obtained by the finite element analysis are reasonable. The finite element method is applied to study the effects of wall panel aspect ratio on the crack length, crack width and location of maximum crack width, which are useful information for the design of crack control steel reinforcement.